Chemical and Bio-Chemical Studies on Some Hybrid Millet Seeds - AGNIHOTRI, ROHITAS; SHRIVASTAVA, S.K. (Asian Journal of Chemistry, 2010)
The millets are very important staple food in the rural parts of India. The three hybrid varieties of millets viz., Ragi (O), Kutki (jk-8) and Kodo (jk-48) were analyzed for their proximate composition and oxalate, tannin and cyanogenetic glucosides content.